Heavy metals in sludge during anaerobic sanitary landfill: Speciation transformation and phytotoxicity. (15th March 2017) - Yang, Kai; Zhu, Ying; Shan, Ranran; Shao, Yanqiu; Tian, Chao
Abstract: Sanitary landfill persists as a predominant sludge disposal method in particular in China. In this study, successive subsurface sludge samples (0.3 m deep) were collected from a bioreactor landfill unit where an anaerobic process took place during a 500 d period. The sludge samples were analyzed for total concentrations of cadmium (Cd), chromium (Cr), copper (Cu), nickel (Ni), lead (Pb) and zinc (Zn) and their species distributions, together with selected sludge chemical properties. In addition, the sludge samples were subjected to phytotoxicity testing. The results showed that the mobilities of Cd and Ni were decreased with landfill time, while the mobilities of Cr, Cu, Pb and Zn remained consistently low over the landfill period. The residual amounts of all these heavy metals were increased with landfill time, suggesting that the anaerobic sanitary landfill is an effective sludge stabilization method to reduce the ecological risk of these heavy metals. The increase in the sludge pH value with landfill time tended to promote the precipitation of heavy metals. Moreover, the sludge stabilization was found to be indicated by the formation of humic substance (HS) and volatilization of volatile matter (VM). The germination index (GI) values of barley ( Hordeum vulgare L.) and Chinese cabbage ( Brassica rapa chinensis ) seeds grown in the 500 d anaerobically stabilized sludge were approximately 5.2- and 4.1-times higher than the values of those grown in the fresh sludge. The final sludge extract did not cause any significant inhibitory effect on the germination of the two types of seeds. Graphical abstract: Highlights: Successive subsurface sludge samples were taken from a bioreactor landfill unit. The ratios of Cd and Ni in mobile fractions were decreased with landfill time. The ratios of Cr, Cu, Pb and Zn in mobile fractions remained consistently low. The sludge stabilization was indicated by the formation of humic substance.